Catheter ablation of atrial fibrillation in patients with heart failure with reduced ejection fraction: Real world experience from six European centers. (25th June 2019) - Providência, Rui; de Asmundis, Carlo; Chun, Julian; Chierchia, Gianbattista; Defaye, Pascal; Anselme, Frédéric; Creta, Antonio; Lambiase, Pier D.; Schmidt, Boris; Chen, Shaojie; Hunter, Ross J.; Combes, Stephane; et al.
Abstract: Introduction: Catheter ablation of atrial fibrillation (AF) has been recently shown to have an impact on the outcome of patients with heart failure and reduced LV ejection fraction (LVEF). We aimed to assess patients with reduced LVEF referred to catheter ablation of AF, and the efficacy and safety of this procedure compared with healthier patients. Methods: 2083 consecutive procedures of catheter ablation of AF in six centers were divided into two groups on the basis of LVEF (≤ vs >35%) and comparisons were performed regarding procedural safety and efficacy. Results: Only 51 (2.4%) of patients had low LVEF. Complication rate was comparable: 8.0% vs 6.9% ( P = .760). Low LVEF patients are more frequently in persistent AF at the time of the procedure, have a higher degree of left atrial dilation, and higher CHA2 DS2 VASc score. The rate of atrial arrhythmia relapse post‐blanking period in the first 12 months was higher in the low LVEF group: 58.0% vs 37.6% ( P < .001). During a median follow‐up of 14 months (IQR 5‐24), after adjusting for all baseline differences, AF duration, paroxysmal AF, CHA2 DS2 VASc score, BMI, and indexed LA volume were independent predictors of relapse. LVEF and LVEF ≤ 35% were not identified as predictors of relapse. Conclusions: Patients with reduced LVEF account for only a minority of patients undergoing catheter ablation of AF. However, ablation appears to be as safe as for the general population, and albeit the efficacy seems lower, this appears to be driven by other comorbidities or features, which are more frequent in this population.